Rhabdomyolysis and Acute Kidney Injury due to Severe Heat Stroke - Máximo H. Trujillo; Carlos Fragachán G. (Case Reports in Critical Care)
We present a case of heat stroke (HS) and acute kidney injury (AKI) due to severe rhabdomyolysis in a 14-year-old previously healthy female patient. When she was practicing strenuous exercise she suffered acute seizures and high fever. These symptoms were followed by coma and multiple organ failure (MOF), which included AKI, encephalopathy, fulminant hepatic failure (FHF), and disseminated intravascular coagulation (DIC). The patient was managed in the ICU with renal replacement therapy, ventilatory support, and other vital supporting measures. After three weeks of ICU treatment she made a full recovery.